Post-Malaria Neurological Syndrome - A Case of Bell’s Palsy After Plasmodium Vivax Malaria - Singh, AK; Chakraborti, S; Subhranag, S (Journal of Nepal Paediatric Society, 2013)
Post-malaria neurological syndrome (PMNS) is defined as the acute onset of neurological or neuropsychiatric syndrome in a patient who had recently recovered from malaria and have negative blood film at the time of onset of neurological symptoms. It is relatively rare, with various clinical symptoms. We report first case of Bell’s palsy developing on 10th day of afebrile period after successful treatment of Plasmodium vivax (P.vivax) malaria and which completely recovered in next two weeks. DOI: http://dx.doi.org/10.3126/jnps.v33i1.6893 J Nepal Paediatr Soc. 2013;33(1):66-67